Dynamics of bacterial functional genes and community structures during rhizoremediation of diesel-contaminated compost-amended soil. Issue 10 (11th October 2021) - Lee, Yun-Yeong; Seo, Yoonjoo; Ha, Minyoung; Lee, Jiho; Yang, Hyoju; Cho, Kyung-Suk
Abstract: The objective of this study was to characterize the effects of organic soil amendment (compost) on bacterial populations associated with petroleum hydrocarbon (PH) degradation and nitrous oxide (N2 O) dynamics via pot experiments. Soil was artificially contaminated with diesel oil at total petroleum hydrocarbon (TPH) concentration of 30, 000 mg·kg-soil −1 and compost was mixed with the contaminated soil at a 1:9 ratio (w/w). Maize seedlings were planted in each pot and a total of ten pots with two treatments (compost-amended and unamended) were prepared. The pot experiment was conducted for 85 days. The compost-amended soil had a significantly higher TPH removal efficiency (51.1%) than unamended soil (21.4%). Additionally, the relative abundance of the alk B gene, which is associated with PH degradation, was higher in the compost-amended soil than in the unamended soil. Similarly, cnor B and nos Z (which are associated with nitric oxide (NO) and N2 O reduction, respectively) were also highly upregulated in the compost-amended soil. Moreover, the compost-amended soil exhibited higher richness and evenness indices, indicating that bacterial diversity was higher in the amended soil than in the unamended soil. Therefore, our findings may contribute to the development of strategies to enhance remediation efficiency and greenhouse gas mitigation during the rhizoremediation of diesel-contaminated soils.